Performance Characteristics of Putative Tests for Subclinical Chorioamnionitis - Rodney K. Edwards; Penny Clark; Gregory J. Locksmith; Patrick Duff (Hindawi Limited, 2001)
Objective: To evaluate amniotic fluid glucose, matrix metalloproteinase (MMP)-9, interleukin (IL)-6, and IL-12 for diagnosing subclinical chorioamnionitis in women with preterm labor.